The fire within - D'Lacey, Chris (New York : Orchard Books, 2005)
When college student David Rain rents a room in an unusual boardinghouse full of clay dragons, he has no idea that they, along with some lively squirrels, will help jumpstart his writing career.
Sequel: Icefire.
630
Accelerated Reader AR
Keywords: Supernatural -- Juvenile fiction; Squirrels -- Juvenile fiction; Dragons -- Juvenile fiction; Authorship -- Juvenile fiction; Boardinghouses -- Juvenile fiction